Modalities of using endodontic nickel-titanium rotary instruments and factors influencing their implementation in dental practice - Ahmad A. Madarati; Adnan A. Habib (BMC, 2018)
Abstract Background To establish the extent of using nickel titanium rotary instruments (NiTi-RIs), to identify reasons for using / not using NiTi-RIs, to explore usage modalities and to identify factors and measures that can increase implementation of NiTi-RIs in general dental practice. Methods Two pilot questionnaires were conducted on academic staff members at College of Dentistry, Taibah University, general dentists (GDs) and endodontists to finalise the questionnaire. A sample size was calculated considering the expected and minimum accepted response rates (60 and 48%, respectively) and a 99.9% Confidence Level. The online-questionnaire was sent to 600 GDs and all endodontists (175) working in Saudi Arabia. A reminder was emailed after 10 weeks to encourage non-respondents to complete the questionnaire. Responses, were collected and converted into numerical data which were analysed using the Chi-square test (p = 0.05). Results Significantly most respondents (71.9%) used NiTi-RIs (p < 0.001); with more endodontists (96.9%) than GDs (60%). Most users (62.5%) had been using NiTi-RIs for More than 3 years (p < 0001). The trend of using NiTi-RIs increased as participants' experience and the number of root-canal treatments performed per week increased (p = 0.021). While most respondents (45.3%) used NiTi-RIs because of faster root-canal preparation, the majority of non-users (85.3%) didn't do so because of high cost. The highest proportion (43.3%) reported better undergraduate education as the most important factor that can significantly increase NiTi-RIs usage. The majority (91.8%) prepared glide-path before using NiTi-RIs; especially with stainless steel hand-files (63.3%). Conclusions NiTi-RIs are relatively well adopted in Saudi dental practice. However, better education, especially during undergraduate training and lower cost can increase their usage. Overall, clinicians showed good awareness of NiTi-RIs usage aspects which reflected on usage modalities.